2010
DOI: 10.1038/ng.723
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of renal cell carcinoma identifies two susceptibility loci on 2p21 and 11q13.3

Abstract: contributed to the design and execution of the overall study. M.P.P., M.J., J.R.T., G.S., L.E.M., L.A.K., X.W., V.G., K.B.J., J.D.M., N.R., S.J.C., and P Brennan contributed to the statistical analysis. M.P.P., M.J., S.J.C. and P. Brennan wrote the first draft of the manuscript. D. Zeleniak, E.P., L.A.K., X.W., K.B.J., S.H.V., S.L.M., Y.Y., A.M.M., E.S.B., N.N.C., M.F., D.L., I.G., S.H., H. Blanche, A.H., G.T., Z.W., M.Y., K.G.S., S.J.C., and M.L. supervised or conducted the genotyping. The remaining authors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
200
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 221 publications
(212 citation statements)
references
References 35 publications
7
200
1
4
Order By: Relevance
“…A cell line was derived from the tumor tissue, and its histone profile is displayed below its matching primary tissue. This enhancer is known to interact with the CCND1 promoter from a previous study (21) and is situated close to an RCC susceptibility SNP rs7105934 (49).…”
Section: Tumor-specific Enhancers Are Associated With Hallmarks Of Ccrccmentioning
confidence: 99%
“…A cell line was derived from the tumor tissue, and its histone profile is displayed below its matching primary tissue. This enhancer is known to interact with the CCND1 promoter from a previous study (21) and is situated close to an RCC susceptibility SNP rs7105934 (49).…”
Section: Tumor-specific Enhancers Are Associated With Hallmarks Of Ccrccmentioning
confidence: 99%
“…A modest proportion (2-4%) of RCC is associated with VHL syndrome caused by germline mutations in VHL 5 . Results from genome-wide association studies have identified common germline variants associated with increased susceptibility for developing ccRCC 6,7 , and recent sequencing efforts have revealed recurrent somatic mutations in a number of genes including PBRM1, SETD2 and BAP1 (ref. 8).…”
mentioning
confidence: 99%
“…According to our RCC GWAS data set, association results for four 5,6 of the five previously reported GWAS-identified RCC susceptibility variants are confirmed (P between 0.011 and 3.0 Â 10 À 4 for SNPs on 2p12, 11q13.3, 12p11.23 and 12q24.31 (Table 1) generated from logistic regression analysis). Logistic regression is used throughout to test for association between SNPs and disease.…”
Section: Gwas Data and Imputation In Icelandic Samplesmentioning
confidence: 85%
“…Rare, high-penetrance mutations accounting for syndromic RCC have been found in several genes, including VHL, MET, FLCN and FH 4 . Genome-wide association studies (GWAS) have reported five sporadic RCC susceptibility loci [5][6][7] . However, in combination, these risk variants account for only a small fraction of the approximately twofold greater than the average risk of RCC in first-degree relatives of RCC patients 1,2 .…”
mentioning
confidence: 99%